Effective Improvement of the Photovoltaic Performance of Carbon-Based Perovskite Solar Cells by Additional Solvents - Zhang, Chenxi; Luo, Yudan; Chen, Xiaohong; Chen, Yiwei; Sun, Zhuo; Huang, Sumei (Nano-Micro Letters, 2016)
A solvent-assisted methodology has been developed to synthesize CH3NH3PbI3 perovskite absorber layers. It involved the use of a mixed solvent of CH3NH3I, PbI2, γ-butyrolactone, and dimethyl sulfoxide (DMSO) followed by the addition of chlorobenzene (CB). The method produced ultra-flat and dense perovskite capping layers atop mesoporous TiO2 films, enabling a remarkable improvement in the performance of free hole transport material (HTM) carbon electrode-based perovskite solar cells (PSCs). Toluene (TO) was also studied as an additional solvent for comparison. At the annealing temperature of 100 °C, the fabricated HTM-free PSCs based on drop-casting CB demonstrated power conversion efficiency (PCE) of 9.73 %, which is 36 and 71 % higher than those fabricated from the perovskite films using TO or without adding an extra solvent, respectively. The interaction between the PbI2–DMSO–CH3NH3I intermediate phase and the additional solvent was discussed. Furthermore, the influence of the annealing temperature on the absorber film formation, morphology, and crystalline structure was investigated and correlated with the photovoltaic performance. Highly efficient, simple, and stable HTM-free solar cells with a PCE of 11.44 % were prepared utilizing the optimum perovskite absorbers annealed at 120 °C.